Recent Advances in the Modeling of Alzheimer’s Disease - Sasaguri, Hiroki; Hashimoto, Shoko; Watamura, Naoto; Sato, Kaori; Takamura, Risa; Nagata, Kenichi; Tsubuki, Satoshi; Ohshima, Toshio; Yoshiki, Atsushi; Sato, Kenya; Kumita, Wakako; Sasaki, Erika; et al. (Frontiers in Neuroscience, 2022)
Since 1995, more than 100 transgenic (Tg) mouse models of Alzheimer’s disease (AD) that overexpress mutant amyloid precursor protein (APP) or APP/presenilin 1 (PS1) cDNAs have been generated. Although many of these models successfully recapitulate major pathological hallmarks of the disease such as amyloid beta peptide (Abeta) deposition and neuroinflammation, they have suffered from artificial phenotypes. To overcome these concerns, we developed single App knock-in mouse models harboring the Swedish and Beyreuther/Iberian mutations with or without the Arctic mutation (AppNL-G-F and AppNL-F mice). These models showed Abeta pathology, neuroinflammation, and cognitive impairment in an age-dependent manner. The model with the Artic mutation exhibits extensive pathology in mice as early as 6 months of age but is unsuitable for investigating Abeta metabolism and clearance because this mutation renders Abeta resistant to proteolytic degradation and prone to aggregation. The weakness of the latter model is that it may take as long as 18 months for the pathology to become sufficiently evident. Nevertheless, this model was successfully applied to modulating Abeta pathology by genome editing, to revealing the role of neprilysin and in Abeta metabolism, and to identifying somatostatin receptor subtypes involved in Abeta bdegradation by neprilysin. We have subsequently generated a new double knock-in line carrying the AppNL-F and Psen1P117L/WT mutations. This model shows greater pathology than the AppNL-G-F line. In addition, we introduce a new model of cerebral amyloid angiopathy. Use of the App knock-in mice also led to identification of the alpha-endosulfine-KATP channel pathway as components of the somatostatin-evoked physiological mechanisms that reduce Abeta deposition via the activation of neprilysin. Such advances have provided new insights for the prevention and treatment of preclinical AD. Because tau pathology plays an essential role in AD pathogenesis, we created human tau knock-in mice, in which the entire murine Mapt gene has been humanized. Using these mice, we discovered the CAPON as a mediator linking tau pathology to neurodegeneration and showed that tau humanization promoted pathological tau propagation. Finally, we describe and discuss the current status of mutant human tau knock-in mice and a non-human primate model of AD that we have successfully created.